Frontispiece: Supramolecular Assemblies with Aggregation‐Induced Emission Properties for Sensing and Detection. Issue 8 (8th February 2022) - Dai, Dihua; Yang, Jie; Yang, Ying‐Wei
Abstract : This article overviews the advanced structures and sensing properties of representative AIE‐active supramolecular assemblies and illustrates the detection mechanism of the established sensing systems for monitoring particular analytes including metal ions, anions, organic pollutants, gases, biomolecules, and heparin drugs. The advantages, accessibility, and challenges of these systems based on commonly used AIE fluorophores are also discussed. For more information, see the Minireview by Y.‐W. Yang et al. on page 22 ff.